Karyotypic patterns of seven species of molossid bats (Molossidae, Chiroptera) - MorielleVersute, E.; VarellaGarcia, M.; Taddei, V. A. (Karger, 1996)
G- and C- banding patterns of seven species of the bat family Molossidae, Eumops glaucinus, E. perotis; Molossops abrasus, M. remminckii, Molossus ater, M. molossus, and Nyctinomops laticaudatus, were identified. Comparisons among the karyotypes of these species showed extensive homologies between E. perotis, M. ater, M. molossus, M. abrasus, and N. laticaudatus, demonstrating inter- and intrageneric conservatism, and a lesser degree of homologies in M. temminckii and glaucinus, reflecting intrageneric variation, Chromosomal variation was due to inversions, Robertsonian rearrangements, translocations, and variations in the location of constitutive heterochromatin and nucleolus organizer regions. The chromosome corresponding to No. 5 in the M. ater karyotype is discussed. We suggest that the Nyctinomops and Molossops karyotypes represent the primitive condition and that Molossus and Eumops have derived karyotypes.